Quantification of seismic potential failure modes in concrete dams. (23rd December 2015) - Hariri‐Ardebili, Mohammad Amin; Saouma, Victor. E.; Porter, Keith A.
Summary: A comprehensive framework for potential failure modes (PFM) identification and quantification of concrete dams subjected to seismic excitation is presented. A quantifiable indicator of PFM is presented in the context of both linear and nonlinear analyses. As an illustrative example, a thin arch dam subjected to a set of ground motions at different seismic intensity levels is investigated and corresponding PFM quantified. An outcome of this analysis is the probabilistic‐based correlation between linear and nonlinear analyses and identification of the optimal intensity measure parameter. This study, is an adaptation and extension of well‐accepted procedures defined by the performance‐based earthquake engineering paradigm in buildings. Copyright © 2015 John Wiley & Sons, Ltd.